Private speech among children with intellectual disabilities - Niu, Ye; Yoshimura, Yuko; Yoshioka, Manabu; Kikuchi, Mitsuru; Kobayashi, Hiroaki (Frontiers in Developmental Psychology, 2025)
IntroductionPrivate speech has been shown to serve as a self-regulatory and planning tool for children during task-solving activities. While both typically developing children and those with neurodevelopmental disorders—such as attention-deficit/hyperactivity disorder and high-functioning autism spectrum disorder (ASD)—have been found to use private speech, the frequency and developmental trajectories vary across groups. However, little is known about private speech in children with intellectual disabilities.MethodsThis study examined private speech in children with intellectual disabilities (n = 20) during a selective attention task. Verbalizations were recorded and categorized based on their relevance to the task.ResultsSeventy percent of the participants used private speech during the task, and 60% produced task-relevant utterances that appeared to assist in problem-solving. Notably, children with stronger ASD characteristics exhibited more frequent use of private speech than those with milder traits.DiscussionThese findings suggest that children with intellectual disabilities engage in private speech during cognitive tasks, and that this speech may function as a tool for behavioral regulation. The increased use among those with pronounced ASD tendencies may reflect differences in cognitive or social processing, underscoring the importance of considering individual variability in educational support.